Single nucleus RNA-sequencing defines unexpected diversity of cholinergic neuron types in the adult mouse spinal cord - Mor R. Alkaslasi (Nature Portfolio, 2021)
The full heterogeneity and different functional roles of cholinergic neurons in the adult spinal cord remain to be defined. Here the authors develop a targeted single nuclear RNA sequencing approach and use it to identify an array of cholinergic interneurons, as well as visceral and skeletal motor neurons.